(untitled) - AYU WIDYANTI, RATNA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract :The purpose of this research is to examine and analyze the effect of profitability proxied by return on equity, dividend payout ratio, and corporate social responsibility disclosure to firm value (Tobin’s Q) of manufacturing sector that listed in Indonesia Stock Exchange period 2010-2012. This study used purposive sampling method and find 15 manufacturing companies as samples. The method of analysis used is multiple linear regression with SPSS version 18. Based on the results of data analysis it can be concluded that profitability proxied by ROE and dividend payout ratio affects firm value proxied by Tobin’s Q, while corporate social responsibility diclosure shows the results has no effect on firm value. Keywords: profitability, dividend payout ratio, corporate social responsibility, and firm value.